A.S.P.E.N. Standards for Nutrition Support: Home and Alternate Site Care. (25th June 2014) - Durfee, Sharon M.; Adams, Stephen C.; Arthur, Elaine; Corrigan, Mandy L.; Hammond, Kathleen; Kovacevich, Debra S.; McNamara, Kevn; Pasquale, Jack A.
Abstract : The American Society for Parenteral and Enteral Nutrition (A.S.P.E.N.) is a professional society of physicians, nurses, dietitians, pharmacists, nurse practitioners, physician assistants, other allied health professionals, and researchers. A.S.P.E.N. envisions an environment in which every patient receives safe, efficacious, and high‐quality nutrition care. A.S.P.E.N.'s mission is to improve patient care by advancing the science and practice of clinical nutrition and metabolism. These combined Standards for Nutrition Support: Home Care and Alternate Site Care are an update of the 2005 and 2006 standards.